PENGEMBANGAN LKPD DIGITAL BERDIFERENSIASI PERILAKU LITERASI MATEMATIS BERBASIS MASALAH PADA MATERI GARIS SINGGUNG LINGKARAN - Putri, Silvinia Eliza (Jurnal Edukasi dan Penelitian Matematika, 2024)
This research aims to develop LKPD differentiated mathematical literacy behavior that is valid, practical and effective. This research is based on the Plomp Model. The instruments used are practicality, validity and interview checklist instruments. The research was carried out in three phases, namely preliminary research; development phase, and assessment phase. In the preliminary research phase, questionnaires were distributed and questions and answers were conducted with educators. The development phase includes LKPD development, LKPD validation, one-to-one evaluation and small group evaluation. Then, in the final phase, a final test was carried out to determine students' mathematical literacy behavior. The validity value obtained by this LKPD is 81.82%, the practicality value of the LKPD is 88.54% at the one-to-one evaluation stage, and 94.62% for the small group evaluation. LKPD can be said to be effective because the average student test result is 1.34. So that the LKPD can be said to be valid, practical and effective.Keywords–  Student worksheets, Differentiated, Mathematical literacy behavior, Problem based